2016
DOI: 10.1089/nat.2016.0606
|View full text |Cite
|
Sign up to set email alerts
|

Cation Coordination Alters the Conformation of a Thrombin-Binding G-Quadruplex DNA Aptamer That Affects Inhibition of Thrombin

Abstract: Thrombin-binding aptamers are promising anticoagulants. HD1 is a monomolecular antiparallel G-quadruplex with two G-quartets linked by three loops. Aptamer-thrombin interactions are mediated with two TT-loops that bind thrombin exosite I. Several cations were shown to be coordinated inside the G-quadruplex, including K, Na, NH, Ba, and Sr; on the contrary, Mn was coordinated in the grooves, outside the G-quadruplex. K or Na coordination provides aptamer functional activity. The effect of other cations on aptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…In this case, however, it seems the thrombin acts as a molecular chaperone by stabilizing G-quadruplex structure and consequently an anticoagulant activity of TBA is retained [ 36 , 37 ]. Importantly, the formation of thermodynamically stable G-quadruplex structure of TBA with disrupted loop geometry could be detrimental for TBA anticoagulant properties [ 38 ]. Taken together, the literature data indicate that thermodynamic stability is not the only factor that determines inhibitory activity of TBA.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, however, it seems the thrombin acts as a molecular chaperone by stabilizing G-quadruplex structure and consequently an anticoagulant activity of TBA is retained [ 36 , 37 ]. Importantly, the formation of thermodynamically stable G-quadruplex structure of TBA with disrupted loop geometry could be detrimental for TBA anticoagulant properties [ 38 ]. Taken together, the literature data indicate that thermodynamic stability is not the only factor that determines inhibitory activity of TBA.…”
Section: Resultsmentioning
confidence: 99%
“…The G-quartets further stack to produce a G-quadruplex structure, generally stabilized by metal cations, e.g., K + , Na + , Ba 2+ , or Sr 2+ , inside the core, though exceptions have been reported 53,54 . However, exceptions to this traditional structural pattern have been observed in many natural/synthetic G-quadruplexes 39,[55][56][57][58] . For example, Krauss et al reported the crystal structure of a thrombin-bound DNA aptamer, in which the orientation of guanine bases broke the Hoogsteen hydrogen-bonded cyclic pattern, but a G-quartet structure was still produced 55 .…”
Section: Resultsmentioning
confidence: 96%
“…NU172. Discovered through SELEX and subsequently truncated to 26 nucleotides, NU172 (ARCA Biopharma) is a DNA aptamer targeting thrombin exosite I [127], able to fold into a G4 structure [128]. In preclinical studies, NU172 has shown the ability to prolong thrombin clotting time.…”
Section: Anticoagulant G4-aptamersmentioning
confidence: 99%